Systematic grant and funding body acknowledgement data for publications: An examination of new dimensions and new controversies for bibliometrics - John Rigby (The University of Manchester, Manchester Business School, 2011)
Bibliographic databases are beginning to provide systematic grant and funding body acknowledgement data for the publications they index. This paper considers how this new data might be used for policy purposes and the key issues that are likely to arise in its use. While the attempt to provide this kind of systematic data is in its relative infancy, there is already sufficient information within the WOS database to examine a number of controversies in science studies. This paper considers one such issue, namely the relationship between the number of funding sources acknowledged and the citation impact of publications where a positive relationship has been assumed to exist. Analyses of sets of publications from 2009 from the journals Cell and Physical Review Letters give contrasting results, suggesting that our understanding of the issue of the relationship between the impact of a publication and the number of funding sources which it acknowledges is not fully understood and may be more complicated that previously considered. It is proposed that scientific research findings are packaged by researchers into papers in a variety of ways for a wide variety of purposes. Individual funding quanta from whatever source are not therefore inputs to papers directly; rather, such funding supports a process that has amongst its outcomes, the production of papers.
Keywords: 330; funding acknowledgement; grant; research; citation; impact